Hubungan Asupan Cairan dan Iklim Kerja dengan Status Hidrasi Pekerja Home Industry Keripik Pisang Lumajang - Amanda Fithri Habibati; Ulfa Lailatus Sa'adah; Lilis Sulistyorini (Universitas Airlangga, 2022)
Background: Most of the body is composed of water. Water is essential for the human body. If water reduction in the human body, dehydration will occur. Therefore it is crucial to meet the needs of fluid consumption. Environmental factors can also cause dehydration, one of which is the work climate. Not all home industries meet the requirements of the work environment and occupational safety and health (OSH) for workersObjectives: To analyze the relationship between fluid intake and work climate with the hydration status of workers in the banana chip home industry LumajangMethods: This research is an observational study. This study uses a quantitative research type as well as a cross-sectional design. Samples were taken by a simple random sampling method so that 26 workers obtained 34 workers in 13 home industries. Univariate analysis with frequency distribution and bivariate with Spearmen rank correlation testResults: There is a relationship between fluid intake (p=0.032) and work climate (p=0.001) with workers' hydration status. A work climate that exceeds the TLV and the need for fluid consumption of fewer than 3.7 liters/day (for men) and 2.7 liters/day (for women) can cause dehydration from mild to severe. Conclusions: It concluded a significant relationship between work climate and fluid intake with workers' hydration status. Because of, hot working environment and insufficient fluid intake for workers, resulting in dehydration of workers. Recommendations are that employers can meet the fluid intake of workers and are easily accessible for workers and install local exhaust ventilation.